2019
DOI: 10.1002/uog.20173
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of adverse perinatal outcome by cerebroplacental ratio in women undergoing induction of labor

Abstract: Objective To investigate the performance of screening for adverse perinatal outcome by the cerebroplacental ratio (CPR) measured within 24 h prior to induction of labor. MethodsThis was a prospective observational study of 1902 singleton pregnancies undergoing induction of labor at ≥ 37 weeks' gestation. Doppler ultrasound was used to measure the pulsatility index (PI) in the umbilical artery (UA) and fetal middle cerebral artery (MCA) within 24 h before induction of labor. The measured UA-PI and MCA-PI and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
4
43
1
1
Order By: Relevance
“…Fiona et al, have examined 1,902 singleton pregnancies undergoing induction of labor at ≥37 weeks' gestation in a prospective analysis. They were able to demonstrate that low CPR, measured within 24 hours of induction of labor, is associated with increased risk of cesarean section for fetal distress and adverse neonatal outcome (8).…”
Section: Discussionmentioning
confidence: 99%
“…Fiona et al, have examined 1,902 singleton pregnancies undergoing induction of labor at ≥37 weeks' gestation in a prospective analysis. They were able to demonstrate that low CPR, measured within 24 hours of induction of labor, is associated with increased risk of cesarean section for fetal distress and adverse neonatal outcome (8).…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome this problem, we decided to investigate the potential value of biomarkers measured within 24 h prior to induction of labor at term. In a previous study of 1902 women with a singleton pregnancy undergoing induction of labor at ≥ 37 weeks' gestation, we found that low CPR was associated with increased risk of Cesarean section for non‐reassuring fetal status in labor and adverse neonatal outcome, but the performance of CPR for such surrogates of adverse perinatal outcome was poor.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies examining the value of low CPR in predicting adverse outcome in pregnancies undergoing induction of labor at ≥ 37 weeks' gestation reported contradictory results 7,16,17 . A study of 19 207 women with a singleton pregnancy undergoing routine assessment at 35-37 weeks' gestation reported that serum PlGF < 5 th percentile and sFlt-1 > 95 th percentile were associated with increased risk of Cesarean delivery for suspected fetal compromise in labor and neonatal unit admission for ≥ 48 h; however, the performance of screening for these adverse outcomes by maternal factors and estimated fetal weight was not improved by the addition of these biochemical markers 18 .…”
Section: Comparison With Findings From Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A relação cerebroplacentária (RCP), ou seja, a divisão entre os índices de impedância da ACM pelos da AU, vem surgindo como um importante preditor de RAP, tanto para fetos restritos como para aqueles adequados para a idade gestacional (AIG). Essa relação representa mais claramente a redistribuição do débito cardíaco fetal secundariamente à hipoxia fetal (Gramellini et al, 1992;Baschat, Gembruch, 2003 Prior et al, 2013;Figueras et al, 2015;Khalil et al, 2015a,b;Morales-Roselló et al, 2015;Bligh et al, 2018b;Dall'Asta et al, 2019;Fiolna et al 2019). Estudos em modelos experimentais também demonstraram melhor correlação entre uma RCP anormal e hipoxia do que os índices individualmente (Arbeille et al, 1995).…”
Section: Who-world Health Organizationunclassified